Detection of Coronary Artery Diseases: Comparative Study of Multidetector Computed Tomography Angiogram (64 slice scanner) and Conventional Angiogram (Cardiovascular Journal, 2012)
Background: Multislice computed tomography (MDCT) is a promising noninvasive method of detecting coronary artery disease. It is not yet being widely used in Bangladesh. We aimed to assess the diagnostic accuracy of the of 64 slice CT in detecting CAD with reference to conventional coronary angiography. Methods: It was cross sectional comparative study conducted in National Institute of Cardiovascular Diseases and Bangabandhu Sheikh Mujib Medical University. Total 80 patients were included in the study who underwent MDCT and coronary angiogram. Results: The sensitivity, specificity, positive predictive value, negative predictive value and accuracy or efficacy for single vessel disease were 87.5%, 96.4%, 91.3%, 94.7% and 93.75% respectively. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy or efficacy for double vessel disease were 84.0%, 94.5%, 87.5%, 92.85% and 91.25% respectively. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy or efficacy for triple vessel disease were 69.5%, 91.22%, 76.19%, 88.13% and 85.0% respectively. Conclusion: Coronary angiography is a promising technology that already appears to have high performance to assess patient base, vessel base and segment base sensitivity, specificity, positive predictive value, negative predictive value and accuracy in detecting coronary artery stenosis. DOI: http://dx.doi.org/10.3329/cardio.v4i2.10455 Cardiovasc. j. 2012; 4(2): 120-126